DAMPAK KEMATANGAN EMOSI DAN DISIPLIN KERJA PADA KINERJA DOSEN DI 4 PTS DI KOTA BANDAR LAMPUNG - Andy FitriyadI Dharma Tilaar (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
Emotional maturity is one's ability to recognize oneself, manage oneself, motivate oneself,recognize the emotions of others (empathy) and the ability to build relationships with others. WhilePerformance is the result of the process of a work activity undertaken based on measurement andassessment of the results of activities.In this research also object of research used is four (4) Private University (PTS) in BandarLampung city, as research object Some of the causal factors used in this research include emotionalmaturity and work discipline as trigger factor which according to some similar research have influenceThe great Sri (1999) and Sia (2001). In terms of the importance of emotional maturity and workdiscipline as an important factor for shaping performance, the research model used is: "The Influence ofEmotional Maturity and Work Discipline on Lecturer Performance in 4 PTSs in Bandar Lampung".Independent variable in this research is emotional maturity and work discipline while performance asdependent variable. Population in this research is university lecturer in Bandar Lampung City whichamounted to 40 people.The result of research data analysis showed that Emotional Maturity and Work Discipline havea moderate influence (72,4%) to Lecturer Performance, with variable of Emotional Maturity as dominantvariable forming Lecturer Performance with contribution of regression coefficient equal to (0,451). ThenCan not eliminate the work discipline caused by Sahih on F test proving and significant with T Testingstudent proof so that all hypothesis accepted.